Metal-free one-pot synthesis of 2-substituted and 2,3-disubstituted morpholines from aziridines - Sun, Hongnan; Huang, Binbin; Lin, Run; Yang, Chao; Xia, Wujiong (Beilstein Journal of Organic Chemistry, 2015)
The metal-free synthesis of 2-substituted and 2,3-disubstituted morpholines through a one-pot strategy is described. A simple and inexpensive ammonium persulfate salt enables the reaction of aziridines with halogenated alcohols to proceed via an SN2-type ring opening followed by cyclization of the resulting haloalkoxy amine.
Keywords: ammonium persulfate; aziridine; metal free; morpholine